2021
DOI: 10.1302/2046-3758.105.bjr-2020-0253.r2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of focused continuous pulsed electromagnetic field therapy on early tendon-to-bone healing

Abstract: Aims Rotator cuff (RC) tears are common musculoskeletal injuries which often require surgical intervention. Noninvasive pulsed electromagnetic field (PEMF) devices have been approved for treatment of long-bone fracture nonunions and as an adjunct to lumbar and cervical spine fusion surgery. This study aimed to assess the effect of continuous PEMF on postoperative RC healing in a rat RC repair model. Methods A total of 30 Wistar rats underwent acute bilateral supraspinatus tear and repair. A miniaturized electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This occurs via regulation of cell proliferation, differentiation, and maturation, particularly in the treatment of musculoskeletal diseases ( Yang et al, 2021 ; Liu et al, 2022 ). PEMF was reported to improve treatment of various bone diseases, such as, cartilage defects, tendon repair, osteoarthritis, osteoporosis, and so on ( Reilingh et al, 2016 ; Wang et al, 2019 ; Dolkart et al, 2021 ). In recent years, clinical studies have shown that PEMF also has a significant relieving effect on the pain caused by IVD degeneration ( Foley-Nolan et al, 1990 ; Sutbeyaz et al, 2006 ; Alvarez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs via regulation of cell proliferation, differentiation, and maturation, particularly in the treatment of musculoskeletal diseases ( Yang et al, 2021 ; Liu et al, 2022 ). PEMF was reported to improve treatment of various bone diseases, such as, cartilage defects, tendon repair, osteoarthritis, osteoporosis, and so on ( Reilingh et al, 2016 ; Wang et al, 2019 ; Dolkart et al, 2021 ). In recent years, clinical studies have shown that PEMF also has a significant relieving effect on the pain caused by IVD degeneration ( Foley-Nolan et al, 1990 ; Sutbeyaz et al, 2006 ; Alvarez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the systemic effects of PEMF on rats, we measured body weight of rats at 2w, 4w and 8w timepoint, and no significance change was observed in each group, which confirmed that PEMF might be a safe noninvasive therapy. It has been shown that PEMF modulates biological functions of many tissues under pathological conditions, including injuries in bones, tendons, muscles and nervous system ( Gessi et al, 2019 ; Huegel et al, 2020 ; Dolkart et al, 2021 ). In this study we mainly focus on the PEMF effect on disc degeneration induced by tail puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dolkart et al (24) also studied the effects of the continuous pulsed electromagnetic feld (PEMF) on rotator cuff (RC) healing using a rat model. In their study, the authors hypothesized that PEMF application after rotator cuff detachment and repair could produce beneficial effects on biomechanical properties, tissue morphology and bone density.…”
Section: Pulsed Electromagnetic Field (Pemf) and Tendon Diseasesmentioning
confidence: 99%
“… 2 Therefore, TBI injury is common and it is difficult for restoration of injured TBI to the native form due to the slow and incomplete regeneration of the junctional fibrocartilage layer at the healing site. 3 , 4 Therapeutic strategies have been attempted to accelerate the tendon-bone (T-B) healing and promote fibrocartilage regeneration, among which postoperative loading exercise is an important part.…”
Section: Introductionmentioning
confidence: 99%